Complex Regional Pain Syndrome after Total Knee Arthroplasty is Rare and Misdiagnosis Potentially Hazardous—Prospective Study of the New Diagnostic Criteria in 100 Patients with No Cases Identified - Kosy, Jonathan D.; Middleton, Simon W. F.; Bradley, Benjamin M.; Stroud, Rowenna M.; Phillips, Jonathan R. A.; Toms, Andrew D. (The Journal of Knee Surgery, 2018)
Previous studies suggest that complex regional pain syndrome (CRPS) occurs in up to 21% of patients following total knee arthroplasty (TKA). However, this diagnosis has a substantial impact on the patient's management if it is incorrect. We aimed to identify cases, using updated internationally accepted criteria, while investigating potential causes of misdiagnosis.We prospectively studied a consecutive series of 100 primary TKA patients. Each patient was assessed 6-week post-TKA. Pain levels were recorded with the presence of symptoms and signs of CRPS (Budapest Diagnostic Criteria) assessed in those with excessive pain. An alternative diagnosis was sought, in these patients, including the presence of neuropathic pain.We found no cases of CRPS (no patients had symptoms or signs in greater than two of four subgroups). Seventeen patients had excessive pain levels (nine had an alternative diagnosis explaining this). The commonest signs were sensory and sudomotor, whereas motor/trophic changes were not seen. Using a previous definition (Orlando Criteria), eight patients may have been diagnosed with CRPS. Over half of the patients with unexplained excessive pain had evidence of neuropathic pain.CRPS is a rare diagnosis following TKA using modern criteria. Isolated signs and symptoms may lead to the overdiagnosis of CRPS in the presence of unexplained pain following TKA. New diagnostic criteria, with strict definitions and treatment algorithms, are now accepted. Delays in managing more common causes (such as neuropathic pain) may negatively affect the patient's outcome.
Keywords: complex regional pain syndrome; total knee arthroplasty; pain; neuropathic pain; diagnostic criteria